PENGARUH LOKASI, EKUITAS MEREK, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL BEKAS - Sumaryanto, Dwi Astutikningsih, Erni Widajanti & (Universitas Slamet Riyadi, 2017)
The purpose of this study is to analyze the effect of location, brand equity, productquality and price on puchase decision used car and analyze the dominant variableinfluence to the purchase decision used car. This study is a survey. The population of theresearch is consumer buyers of used car Bursa Mobil Bekas Sriwedari Surakarta. Thesample was 100 people with convenience sampling technique. Data collection techniquesused questionnaires, observations and literature studies. Data analysis techniques usedmultiple linear regression. The results showed that the location has significant effect onthe purchase decision of used car. Brand equity has significant effects effect on thepurchase decision of used car. Product quality has significant effect on purchasedecision of used car. Price has significant effect on purchase decision of used car.Product quality is the dominant variable affecting the purchase decision of used car.Keywords: location, brand equity, product quality, price, purchase decision